Cannabidiol alters mitochondrial bioenergetics via VDAC1 and triggers cell death in hormone-refractory prostate cancer. (March 2023) - Mahmoud, Ali Mokhtar; Kostrzewa, Magdalena; Marolda, Viviana; Cerasuolo, Marianna; Maccarinelli, Federica; Coltrini, Daniela; Rezzola, Sara; Giacomini, Arianna; Mollica, Maria Pina; Motta, Andrea; Paris, Debora; Zorzano, Antonio; et al.
Abstract: In spite of the huge advancements in both diagnosis and interventions, hormone refractory prostate cancer (HRPC) remains a major hurdle in prostate cancer (PCa). Metabolic reprogramming plays a key role in PCa oncogenesis and resistance. However, the dynamics between metabolism and oncogenesis are not fully understood. Here, we demonstrate that two multi-target natural products, cannabidiol (CBD) and cannabigerol (CBG), suppress HRPC development in the TRansgenic Adenocarcinoma of the Mouse Prostate (TRAMP) model by reprogramming metabolic and oncogenic signaling. Mechanistically, CBD increases glycolytic capacity and inhibits oxidative phosphorylation in enzalutamide-resistant HRPC cells. This action of CBD originates from its effect on metabolic plasticity via modulation of VDAC1 and hexokinase II (HKII) coupling on the outer mitochondrial membrane, which leads to strong shifts of mitochondrial functions and oncogenic signaling pathways. The effect of CBG on enzalutamide-resistant HRPC cells was less pronounced than CBD and only partially attributable to its action on mitochondria. However, when optimally combined, these two cannabinoids exhibited strong anti-tumor effects in TRAMP mice, even when these had become refractory to enzalutamide, thus pointing to their therapeutical potential against PCa. Graphical Abstract: ga1